A study of reflection phase of reflectarray antennas with high loss organic substrates - M. Y. Ismail; H. I Malik; S. R. Masrol; Sharmiza Adnan (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This paper presents an analysis of reflection phase of reflectarray antenna based on high loss organic substrate material. Paper substrate material derived from recycled materials was characterized for dielectric material properties. The material shows excellent dielectric material properties with permittivity of 1.63 and loss tangent of 0.048. Effect of substrate height variation over the reflection phase has been discussed. Full wave analysis of the simulated model depicts that the reduction in substrate height after a certain point results in reflection phase distortion of reflectarray element. Validation of the results has been done by simulation, fabrication and scattering parameters measurements of a rectangular patch element on proposed substrate material. The results show a broadband frequency response of 355 MHz and a phase range of 301º at a phase gradient of 0.14 º/MHz.